Prevalence of dermatoses in adult migrant workers attending dermatology OPD in a tertiary care centre in Puducherry - Sampadarao, Bhavana; Kumar, Govardhan J.; Kaliaperumal, Damayandhi; Dileep, Jude E.; Sekar, Sucharita; Parthasarathi, Umadevi K. (International Journal of Research in Dermatology, 2021)
Background: Migrant workers are exposed to dangerous and unhygienic work environments, which puts them at risk of developing skin diseases. This study aims to assess the prevalence of skin diseases and provide epidemiological data regarding various dermatoses among migrant workers in Puducherry. Methods: This is a hospital-based, cross-sectional study conducted in Aarupadai Veedu Medical College and Hospital from August 2019 to February 2021. 350 migrant workers were randomly selected and examined for the prevalence of infective and non-infective dermatoses. The observations were documented and data were analyzed using statistical package for the social sciences (SPSS) version 22. Results: A total of 350 migrant workers were included in the study. Of most migrants, 90.9% (n=318) were males, while the remaining 9.1% (n=32) were females. The prevalence of infective dermatoses was found to be 76% (n=266) and the prevalence of non-infective dermatoses was 43.10% (n=151) in this study. Fungal infections are the most common infective dermatoses affecting 51.5% of the workers, followed by bacterial skin lesions in 27.4%. Conclusions: This study reveals a high prevalence of infective and non-infective dermatoses among migrant workers, with fungal infections being the most commonly occurring infective skin disease. Eczema was the commonly occurring non-infective dermatoses, according to this study.